ODPOWIEDZIALNOŚĆ ‘AGRIMENSORES’ A ODPOWIEDZIALNOŚĆ GEODETÓW - Sitek, Bronisław (Zeszyty Prawnicze, 2016)
THE LIABILITY OF THE ‘AGRIMENSORES’ AND SURVEYORS’ LIABILITY Summary The agrimensores played an important role in the society of ancien Rome. They were highly respected for their technical skills and knowledge of mathematics. The grounds for the liability of the agrimensores were material damage caused intentionally by surveyor (dolus) and intent to deceive (fallere). An agrimensor was not liable for damage caused as a result of lack of knowledge or experience (imperitia). If several agrimensores onducted the surveying activities they were jointly liable (in solidum), regardless of their individual contribution to the damage. This type of liability could not be used when it was not possible to assign blame to one of the agrimensores. An agrimensor who had a slave to do the measuring held the liability and could not resort to noxal responsibility. Noxal responsibility could be applied if the shoddy work had been performed by a slave; in such cases the party suffering the damage could obtain dominion over the slave who had caused it or receive full compensation from the slave’s owner. The injured party could seek compensation on the grounds of a praetorian actio in factum. The injured party and his heirs had the right to submit a claim, which was subsidiary and therefore penal in nature, which meant it could not be brought against the heirs of the perpetrators. Actio in factum was used as an actio utilis and actio ad exemplum in other similar cases in surveying activities, such as when measuring wine or grain. Nowadays a surveyor’s liability is civil, criminal, administrative or disciplinary. The first two types are important when a specific injury or offence occurs. In such cases only a surveyor who carried out the surveying or cartographic activities on his own is liable. The study shows that, despite some similarities, there are differences between the liabilities of Roman agrimensores and of modern surveyors. Roman law used a system of praetorian civil liability which was penal in character, while today we have a stratified system of liability of up to four separate levels, where the injured party may use only one or submit a cumulative claim, seeking civil damages, and claiming punishment for the perpetrators under criminal law and/or disciplinary proceedings.